2021
DOI: 10.3389/fnins.2021.668852
|View full text |Cite|
|
Sign up to set email alerts
|

Top-Down Proteomics of Human Saliva Highlights Anti-inflammatory, Antioxidant, and Antimicrobial Defense Responses in Alzheimer Disease

Abstract: Alzheimer disease (AD) is the most prevalent neurodegenerative disease in the elderly, characterized by accumulation in the brain of misfolded proteins, inflammation, and oxidative damage leading to neuronal cell death. By considering the viewpoint that AD onset and worsening may be influenced by environmental factors causing infection, oxidative stress, and inflammatory reaction, we investigated the changes of the salivary proteome in a population of patients with respect to that in healthy controls (HCs). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 76 publications
9
49
2
Order By: Relevance
“…An increasing line of evidence indicated that α- and β-defensins can be considered as good biomarkers for AD diagnosis. In particular, the levels of α-defensins 1–2 appear to be high in saliva, blood, serum, and CFS of AD patients [ 43 , 94 , 95 ], the levels of α-defensin 3 in saliva, serum, and CFS [ 43 , 94 , 95 ], whereas the level of α-defensin 4 only in saliva [ 43 ]. In the same manner, an increased level of β-defensin 2 in the serum and CFS of AD patients has been reported compared to healthy controls [ 95 ].…”
Section: Amps Involvement In Admentioning
confidence: 99%
See 4 more Smart Citations
“…An increasing line of evidence indicated that α- and β-defensins can be considered as good biomarkers for AD diagnosis. In particular, the levels of α-defensins 1–2 appear to be high in saliva, blood, serum, and CFS of AD patients [ 43 , 94 , 95 ], the levels of α-defensin 3 in saliva, serum, and CFS [ 43 , 94 , 95 ], whereas the level of α-defensin 4 only in saliva [ 43 ]. In the same manner, an increased level of β-defensin 2 in the serum and CFS of AD patients has been reported compared to healthy controls [ 95 ].…”
Section: Amps Involvement In Admentioning
confidence: 99%
“…Other findings indicated that both cystatin A and cystatin B are also two regulation factors of inflammation that can inhibit cathepsins [ 104 ]. In particular, cystatin B may play a protective role in AD through the inhibition of cathepsin B, a β-secretase enzyme that cleaved APP to synthesize Aβ fragments [ 43 , 105 ]. Interestingly, cathepsin B is overexpressed following chronic exposure to some bacteria producing an AD-like phenotype [ 106 ].…”
Section: Amps Involvement In Admentioning
confidence: 99%
See 3 more Smart Citations